Surveys of Malay medical manuscripts collection in Luzon, Sumatera and Singapore - Mohd Shafri, Mohd Affendi (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2014)
INTRODUCTION: Medical manuscripts contain primary source of information regarding the philosophy, ethics and medical practice of medical practitioners and their epochs. They are now increasingly important in the race to find new pharmaceutical candidates from natural flora and fauna. Medical manuscripts of the Malay world, however, have not received due attention due to lack of interest, and unfamiliarity of the subject among Malay intellectuals. Collections of Malay medical manuscripts are either neglected or unidentified in many centres throughout the world. MATERIALS AND METHODS: Three collection and condition survey visits were made during 2014 (self-arranged, self-funded) to the following collection centres: (a) the Philippines: (i) Trinidad Pardo de Tavera Collection and (ii) the American Historical Collection at the Ateneo de Manila University, Manila, Luzon; (b) Sumatera: (i) Museum Negeri Banda Aceh, (ii) Pusat Dokumentasi dan Informasi Aceh, (iii) Yayasan Perpustakaan dan Museum Ali Hasjmy and (iv) Rumoh Manuskrip Aceh, Banda Aceh, Sumatera; and (c) Singapore: Archive Collection at Masjid Ba’alawi, Singapore. RESULTS AND DISCUSSION: Despite housing the largest indigenous Philippines-related materials, the Philippines visit (early January 2014) yielded not a single unit of manuscript written in Malay or on Malay medicine. During the second visit to Sumatera (early September 2014), new materials were identified and will be part of future cataloguing and digitalization projects. Some manuscripts were re-categorised as non-medical, while others were found missing. The Singapore visit (late September 2014) was also fruitful as one previously unknown but well preserved 19th century medical manuscript was found in the collection, allowing an insight into the practice of Malay medical practitioner in the area. CONCLUSION: These visits highlighted the need for continuous update on the accuracy of previous cataloguing works and continuous collection and condition surveys to identify new materials, resolve conservation threats and analyse known materials.